Kewenangan dan Inklusi Desa - Simarmata, Rajanner P. (Jurnal Wahana Bina Pemerintahan, 2016)
The issues of Law No. 6 of 2014 About the village, showing the spirit of the government to promote the village through exhumation values of lokal customs and wisdom in governance villages by providing broad authority that is authorized by the right of the origin village and village authority of local scale. Article 18 B of the 1945 Constitution is the basis for regulating and developing villages in the future, which has been giving wide space to the village for inreasing into a strong, Forward, independently and democratic to realize the community fair, prosperous and prosper without loss, throught recognition and respect for the autonomy of the State agains the village, with the authoritu to regulate and manage government affairs and public interest by the authority based on the origin and authority right scale local villages as well as other authorities through the assignment of central and local goverment. Based on article 18 B of the 1945 Constitution and the regulations in law No. 6 of 2014 About Village, should develop village into an inclusion environtment that is able to accept diversity and participation of all citizens, so that no citizen or group of citizen are marginalized